A simultaneous disulfide bond cleavage, N, S-bialkylation/N-protonation and self-assembly reaction: syntheses, structures and properties of two hybrid iodoargentates with thiazolyl-based heterocycles. Issue 47 (18th November 2016) - Liu, Guang-Ning; Li, Ke; Fan, Qing-Shun; Sun, Hui; Li, Xin-Yu; Han, Xiao-Nan; Li, Yu; Zhang, Zhen-Wei; Li, Cuncheng
Abstract : Unprecedented multiple in situ reactions were found during preparation of hybrid iodoargentates. Abstract : Solvothermal reactions of AgI with the vulcanization accelerator 2, 2′-dibenzothiazolyl disulfide and hydroiodic acid in alcohols afford two hybrid iodoargentates with one-dimensional structures, namely (Et2 mbt)[Ag2 I3 ] (1, Hmbt = 2-mercaptobenzothiazole) and {(Hmbt)[AgI]} n (2 ). The syntheses of both1 and2 involve unprecedented multiple in situ reactions. Specifically, a simultaneous disulfide bond cleavage, N and S donor atoms bialkylation, and self-assembly reaction lead to1 that contains a discrete N, S-biethylated cation (Et2 mbt) + and a rare inorganic (Ag2 I3 ) − anionic chain, while a simultaneous disulfide bond cleavage, N -protonation and self-assembly reaction affords2 which features zwitterionic Hmbt molecules coordinating with the opposite side Ag atoms of a neutral inorganic (AgI) n chain via forming Ag–S coordination bonds. The simultaneous alkylation on a thiazolyl-N donor and a thiol-S donor atom for a thiazolyl-based heterocycle using inexpensive alcohols and haloids under solvothermal conditions instead of traditional two-step organic synthesis was found for the first time. The two compounds have band gaps of 2.95 eV for1, and 2.78 eV for2 exhibiting an observed blue shift compared with bulk AgI. Also, 1 and2 can be used as effective heterogeneous photocatalysts for methyl orange dye treatment under UV light irradiation.